The Role Of Local Government, SME's and Cooperatives In Realizing A People's Economy In Indonesia - Nara Uran, Alfonsus Vianey (SMARTINDO, 2023)
The populist economic system has been defeated by a liberal economic system that controls almost all countries, even though Indonesia has long known a populist-based economic system which pays attention to the culture of an Indonesian nation. Economic Democracy is taken from the values ​of the Indonesian Nation, the populist economic system has been in effect since 1998, at that time the government was determined to implement a populist economic system with the issuance of MPR Decree No. . Democracy is oriented towards development and various freedoms that are in favor of the interests of the people. people's economy is developed as an effort to further advance society. The method used is descriptive research method because this research aims to obtain answers related to one's opinions, responses or perceptions so that the discussion must be qualitative or use descriptive words. Descriptive research tries to find appropriate and adequate descriptions of all activities, objects, processes and people. The results of the study show that the concept of populist economy is carried out as a development strategy that prioritizes the welfare of the Empowerment community. populist economy can be realized by rearranging political institutions at the district level. Thus the issue of people's economic development cannot be separated from political institutions at the district level. For this reason, it must create a conducive political climate for people's economic development. SMEs, cooperatives, local and central government, food security supports the running of several people's economic activities in Indonesia, when the economic crisis hit Indonesia, large companies experienced a downfall and many went out of business, while SMEs and cooperatives remained strong and even existed at that time.